2017
DOI: 10.1634/theoncologist.2016-0347
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Temozolomide Maintenance Therapy in Newly Diagnosed Glioblastoma

Abstract: Our data do not support a general extension of TMZ maintenance therapy beyond six cycles. 2017;22:570-575 IMPLICATIONS FOR PRACTICE: Radiation therapy with concomitant and adjuvant temozolomide (TMZ) maintenance therapy is still the standard of care in patients below the age of 65 years in newly diagnosed glioblastoma. However, in clinical practice, many centers continue TMZ maintenance therapy beyond six cycles. The impact of this continuation is controversial and has not yet been addressed in prospective ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…Such approach appeared to be effective for primary [54] and recurrent glioblastoma [55][56][57]. Also prolonged (> 6 cycles) standard TMZ therapy was proven to be successful [58,59]. There are data showing that this result does not depend on MGMT promoter methylation [55,60], but other indicate such connection [8].…”
Section: Discussionmentioning
confidence: 99%
“…Such approach appeared to be effective for primary [54] and recurrent glioblastoma [55][56][57]. Also prolonged (> 6 cycles) standard TMZ therapy was proven to be successful [58,59]. There are data showing that this result does not depend on MGMT promoter methylation [55,60], but other indicate such connection [8].…”
Section: Discussionmentioning
confidence: 99%
“…One of them included the dose-dense TMZ to deplete MGMT in tumor cells by continuous daily TMZ treatment 19 , which failed to demonstrate improved efficacy in a phase III clinical trial 20 . Another approach was to extend the cycle of adjuvant TMZ treatment 8,2124 . Hau et al .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between number of adjuvant cycles received and outcome has not been clearly elucidated. Three studies found that patients who received more than 6 cycles of TMZ had improved survival compared to those who received less [15][16][17], while two other studies found no survival difference between these two groups of patients [18,19]. Taken together, these suggest that an as yet unidentified subset of patients may derive benefit from more than 6 cycles of TMZ and drive this difference when observed.…”
Section: Methods and Findingsmentioning
confidence: 97%